The motivation and impact of pension fund activism - Guercio, D (Journal of Financial Economics, 1999)
Pension funds have pursued an active role in corporate governance, although some question their effectiveness and motivations. We examine the impact and motivation of pension fund activism by studying the shareholder proposals of the largest, most active funds from 1987 through 1993. We find significant heterogeneity across funds in activism objectives, tactics, and impact on target firms, consistent with differing investment strategies. We find the funds are more successful at monitoring and promoting change in target firms than previously recognized. We also find no evidence to support motivations other than fund value maximization.